A snapshot of relativistic motion: visualizing the Terrell-Penrose effect - Dominik Hornof; Victoria Helm; Enar de Dios Rodriguez; Thomas Juffmann; Philipp Haslinger; Peter Schattschneider (Communications Physics)
Abstract In 1959, Roger Penrose and James Terrell independently predicted that the Lorentz contraction of fast moving objects is not visible in a snapshot photograph. Rather, the object would appear rotated. This surprising effect has never been tested experimentally. Here we demonstrate the Terrell-Penrose effect in a laboratory setting. Using ps-laser pulses and ultra-fast photography with gating times as short as 300 ps, we achieve a virtual reduction of the speed of light to less than 2 m/s, enabling the visualization of relativistically moving objects in real time. Our results comprise simulations and experimentally synthesized snapshots of a sphere and a cube, which are animated to create a slow-motion effect for velocities close to the speed of light. An extension of our method to otherwise unobservable relativistic phenomena, e. g. the famous “train” thought experiment revealing the constancy of the speed of light, appears feasible.